Exploring the Correlates to Depression in Elder Abuse Victims: Abusive Experience or Individual Characteristics? - Santos, Ana João (Journal of interpersonal violence, 2021)
Depression and depressive symptoms have been studied both as risk factors and consequences of elder abuse, even though the most common cross-sectional design of the studies does not allow inferring cause or consequence relationships. This study estimates the proportion of older adults who screened positive for depressive symptoms among those self-reporting elder abuse and examines whether individual characteristics and/or abusive experience aspects are associated with self-reported depressive symptoms. Participants were 510 older adults self-reporting experiences of abuse in family setting enrolled in the cross-sectional victims’ survey of the Aging and Violence Study. Depressive symptoms were assessed through the abbreviated version of the Geriatric Depression Scale (GDS-5). Poisson regression was used to determine the prevalence ratio (PR) of screening depressive symptoms according to individual and abusive experience covariates: sex, age group, cohabitation, perceived social support, chronic diseases, functional status, violence type, perpetrator, and number of conducts. Women (PR = 1.18, 95% confidence interval [CI] = [1.04, 1.35]) individuals perceiving low social support level (PR = 1.36, 95% CI = [1.16, 1.60]) and with long-term illness (PR = 1.17, 95% CI = [1.02, 1.33]) were found to be associated with increased risk for screening depressive symptoms. In regard to abusive experience, only the number of abusive conducts increased the PR (PR = 1.07, 95% CI = [1.05, 1.09]). Routine screening for elder abuse should include psychological well-being assessment. Interventions toward risk alleviation for both mental health problems and elder abuse should target women perceiving low social support level and with long-term illness.